A molecular conception of organisms and neoplasms : a theory that any organism is basically a single chemical molecule, put forward as the key to the problem of the causation of neoplasms - Cleave, T. L. (Thomas Latimer) (John Wright & Songs, Ltd., 1955)
A Molecular Conception of Organisms and Neoplasms is a six-chapter thesis that consists of a chain of reasoning on the theory of molecular conception. This thesis contends that any organism, even if multicellular, is basically a single molecule, which is the key problem of the causation of neoplasms. After providing a unifying definition of a molecule, this book goes on discussing the concept of fundamental unicellularity of multicellular organism through protoplasmic continuity between its cells. The succeeding chapters highlight the principles of the molecular conception of organisms and n.